Hyoid displacement during swallowing function for completely edentulous subjects rehabilitated with mandibular implant retained overdenture - Ibrahim, Abdallah Mohammed; Elgamal, Mohamed; Abdel-Khalek, Elsayed Abdallah (BMC oral health, 2024)
Background Hyoid bone is attached to the mandible, tongue, larynx, temporal bone, and cervical spine via different types of muscles or ligaments. The tongue, mandible, and hyoid system play a crucial role in swallowing function. This within subject study aimed to evaluate the impact of mandibular implant overdentures on the displacement of the hyoid bones during the swallowing process. Methods Twenty five healthy edentulous subjects were selected for participating in the study. New complete dentures were constructed for all the participants. Subsequently two dental implants were inserted in the canine regions of the participant’s mandibular arch. In order to retain the mandibular prosthesis in place, ball attachments were incorporated into the mandibular dentures to convert them into implant overdentures. Using 10 ml of thin liquid bolus, videofluoroscopy swallowing examination was performed in three different oral conditions: without complete dentures (WCD), with complete denture (CDs), and with a mandibular implant overdenture (IODs). ANOVA with Bonferroni test was used to analyze the data in order to determine how the hyoid displacement varied throughout different oral conditions. Results Compared to complete dentures, mandibular implant overdentures showed a significant decrease ( P < 0.05) in both anterior hyoid displacement and duration of hyoid maximum anterior excursion (DOHMAE). However, there was a non-significant difference ( P > 0.05) between the two oral circumstances in terms of superior hyoid displacement or duration for hyoid maximum elevation (DOHME). There is no penetration or aspiration for both complete denture and implant overdenture oral conditions. Conclusion Implant retained overdentures have a positive effect on hyoid displacement during swallowing of thin liquid bolus consistency relative to conventional complete dentures. Trial registration Retrospectively registered (NCT06187181) 02/1/2024.